2021
DOI: 10.3389/fphys.2021.619722
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Autonomic Function Analysis via Heart Rate Variability Associated With Motor Activity of the Human Colon

Abstract: The parameters of heart rate variability (HRV) can non-invasively assess some autonomic activities, and HRV is influenced by many bodily actions. Although parasympathetic activity is the primary driver of colonic propulsive activity, and sympathetic activity a major inhibitor of colonic motility, they are rarely measured and almost play no role in diagnosis of colon motor dysfunction or in standard treatments. Here we set out to optimize HRV analysis of autonomic nervous system changes related to human colon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Whereas in other studies, the LF component of HRV has been found to be not sensitive enough to assess the sympathetic activity. 24 Indeed, heart rate oscillations in the LF zone are related to the activity of the baroreflex system 25 and both the parasympathetic and sympathetic systems are thought to be involved. As a consequence, the LF/HF ratio should be interpreted with caution, taking into consideration all these limitations and contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in other studies, the LF component of HRV has been found to be not sensitive enough to assess the sympathetic activity. 24 Indeed, heart rate oscillations in the LF zone are related to the activity of the baroreflex system 25 and both the parasympathetic and sympathetic systems are thought to be involved. As a consequence, the LF/HF ratio should be interpreted with caution, taking into consideration all these limitations and contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the Baevsky Index or Sympathetic Index (SI) was calculated to represent sympathetic tone according to the formula . The most frequent RR interval was transformed into the mode (Mo), which is expressed in seconds ( Ali et al, 2021 ). A 50 ms bin width was used for calculating the amplitude of mode (AMo), which is expressed as a percentage of the total number of intervals measured.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with chronic constipation may not be able to generate spontaneous bowel movements. Constipation is the inability to generate one or more defecation reflexes that are orchestrated by the extrinsic autonomic nervous system involving propulsive motor activity and anal sphincter relaxation ( Bharucha et al, 1993 ; Rao et al, 2016 ; Camilleri et al, 2017 ; Callaghan et al, 2018 ; Milkova et al, 2020 ; Ali et al, 2021 ). A propulsive colonic motor pattern may start with triggering of afferent neurons whose cell bodies lie within the DRG of the lumbar and sacral portions of the spinal cord ( Brookes et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…HRV analysis is explored to evaluate autonomic functioning and dysfunction ( Shields, 2009 ; Huizinga et al, 2018 ; Barbier et al, 2022 ; Liu et al, 2022 ). We used HRV successfully to show that propulsive motor patterns generated by the human colon are associated with an increase in parasympathetic activity and a decrease in sympathetic activity ( Yuan et al, 2020 ; Ali et al, 2021 ). HRV is also used to assess success of treatment of autonomic dysfunction in animal models ( Ouyang et al, 2020 ) and human studies ( Karpyak et al, 2004 ; Euteneuer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation